NEW SPECIES OF LABISIA (MYRSINACEAE) FROM SUMATRA - Bambang - Sunarno (BRIN Publishing (Penerbit BRIN), 2002)
SUNARNO, BAMBANG. 2002. New species of Labisia (Myrsinaceae) From Sumatra. Reinwardtia 12(1): 121– 124. ? Three new species L. posthumusiana, L. steenisiana and L. sumatrensis are described